PHYTOCHEMICAL SCREENING AND EVALUATION OF LEAF PARTS OF HYPOESTES PHYLLOSTACHYA ROSEA FOR IN VITRO ANTIOXIDANT ACTIVITIES - JACOB, JENSON; JOHN, MEENU (International Journal of Current Pharmaceutical Research, 2020)
Objective: The aim of this study was focussed on phytochemical analysis, in vitro antioxidant activities of different solvent extracts of Hypoestes phyllostachya leaf. Methods: The leaves were washed efficiently, shade dried and coarsely powdered. The powdered leaf material of Hypoestes phyllostachya was successively extracted with hexane, chloroform, methanol and water using Soxhlet apparatus. Preliminary phytochemical screenings for polyphenolics, proteins, phytosteroids, flavonoids, tannins, glycosides, alkaloids carbohydrates, polyphenolics, saponins were done by following standard procedure. In vitro antioxidant activities of various solvent extracts were assessed using DPPH, ABTS, Hydroxy radical, total antioxidant capacity and reducing power assay. Polyphenolics and flavonoids were also estimated. Results: The results showed that most of the phytochemical compounds such as carbohydrates, proteins, steroids, fixed oils and fatty acids, flavonoids, alkaloids, saponins, tannins, polyphenolics and glycosides present in the methanolic and aqueous extract of Hypoestes phyllostachya. The in vitro antioxidant activity of Hypoestes phyllostachya leaf clearly showed that it has better antioxidant activity, which was confirmed by different assays. Conclusion: From this work, it can be concluded that Hypoestes phyllostachya has the potential to be a good antioxidant but have only a lesser amount of flavonoids and polyphenolic contents. This was the first report on the pharmacological activity of the Hypoestes phyllostachya.